Creation Source of Unan-unan Offering Ideas with Computer Embroidery Techniques Using Suede Fabric on the Vest - El Rahma, Silvia Aisyah; Nahari, Inty; Mayasari, Peppy; Marniati4, Marniati (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Developments in the fashion world continue to experience significant progress, one of which is in the field of fashion. This study aims to formulate the process of creating the source of the idea of offering Unan-unan with a computer embroidery technique using suede fabric on the finished vest, and to find out how the resulting result of the creation of the source of the idea of offering Unan-unan with the computer embroidery technique using suede cloth on the finished vest is relevant based on the Practice-Ied Research method. The result of the creation of the source of the idea of the Unan-unan offering with a computer embroidery technique using suede material in the finished result of this vest is inspired by the head of the buffalo from the traditional ceremony offering of the unan-unan which is considered the highest position animal by the Tengger people because the buffalo is the largest, strongest, and most helpful animal for humans. The application of the buffalo head as an embroidery motif is a form of appreciation and preservation of the original culture of the tengger tribe, namely the unan-unan ceremony in the form of a vest.